Pengaruh Perilaku Asertif Dan Percaya Diri Terhadap Hasil Belajar Ekonomi Siswa Fase F IPS Di SMA Negeri 2 Painan - Renzami Zulmia Putri; Agussalim; Reni Respita (Kilau Publishing, 2025)
This study examines the partial and simultaneous effects of assertive behavior and self-confidence on the economics learning outcomes of Phase F social studies students at SMA Negeri 2 Painan. The research used a quantitative approach with a population of 70 students and employed saturated sampling. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS version 25. Hypotheses were tested using the t-test for partial effects and the F-test for simultaneous effects. The results show that assertive behavior has a positive and significant effect on economics learning outcomes (t = 4.037; p = 0.000 < 0.05). Self-confidence also has a positive and significant effect (t = 2.767; p = 0.007 < 0.05). Simultaneously, assertive behavior and self-confidence have a positive and significant effect on economics learning outcomes (F = 29.133; p = 0.000 < 0.05). In conclusion, higher levels of assertive behavior and self-confidence are associated with better economics learning outcomes among students at the school.